2020
DOI: 10.3389/feart.2020.00280
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes of Particle Flux in the Canary Basin Between 1991 and 2009 and Comparison to Sediment Trap Records Off Mauritania

Abstract: Eastern Boundary Upwelling Ecosystems (EBUEs) are associated with high biological productivity, high fish catch and they highly contribute to marine carbon sequestration. Whether coastal upwelling has intensified or weakened under climate change in the past decades is controversially discussed and different approaches (e.g., timeseries of chlorophyll, wind, sea surface temperature, modeling experiments) have been considered. We present a record of almost two decades of particle fluxes (1991-2009) from ca. 600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 84 publications
4
5
0
Order By: Relevance
“…Based on results obtained during the same cruise, Gómez-Letona et al (submitted) reported intense fluorescence signals of labile, protein-like dissolved organic matter at stations 8, 9, 11 and 12 for the entire water column. These findings suggest a remarkable vertical transport of organic matter from the surface into the dark ocean in the Guinea Dome-Cape Blanc region, in agreement with previous studies with sediment traps reporting high sinking particle fluxes (Fischer et al 2020).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on results obtained during the same cruise, Gómez-Letona et al (submitted) reported intense fluorescence signals of labile, protein-like dissolved organic matter at stations 8, 9, 11 and 12 for the entire water column. These findings suggest a remarkable vertical transport of organic matter from the surface into the dark ocean in the Guinea Dome-Cape Blanc region, in agreement with previous studies with sediment traps reporting high sinking particle fluxes (Fischer et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Besides the vertical variability, latitudinal gradients were observed in the deep ocean, matching surface productivity gradients, as defined by Chl-a concentrations. The tendency to more abundant, more viable and smaller cells in the mesopelagic and bathypelagic layers under highly productive surface waters with potentially important vertical flux of particles (Fischer et al 2020) suggests a remarkable effect of sinking particles in the prokaryotic communities of the dark ocean. In particular, such relationship between surface productivity and prokaryotic viability in deep waters has not been previously reported to the authors’ knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coastal upwelling currents also affect the transport of particulate carbon. Fischer et al (2020) found a similar result, despite significant differences observed in different regions, the particulate carbon flux usually increased in springs since 2005. Phytoplankton under seawater was also found to have carbon sequestration potential, and estimates of the subscale rates of ascidians, ctenophores, ascidians, and pteropods show that their carbon sequestration capacity cannot be ignored and should be included in the carbon sink quantification model (Lebrato et al, 2013).…”
Section: Introductionsupporting
confidence: 66%